Students’ internal world and its evolvement during the study at university - Mykhailichenko, V.; Gren, L. (Problems of Engineer-Pedagogical Education, 2018)
The article reveals the contents of a person’s internal world and the role of education system in its formation in the course of study. The higher educational establishment is a formation and development of students’ professional self-consciousness where success of their activity depends of a great extent. In this connection, the study of a student’s needs-andmotivation sphere, their formation for directedness at successful professional activity is actual and topical. There is shown the role of students’ aims-formation which integrates the structure of regulatory processes into the whole. There is noted the role of convictions which in many respects determine the value attributed by us to processes, and lay at the foundation of motivation, supporting or repressing some or other abilities and behaviors. There is also revealed the contents of value-and-notional approach to the teacher’s personality which enhances the disclosure and realization of their potential, acquiring of new senses of pedagogic activity. The proposed technologies favorably influence the value-and-notional component of not only students’ internal world, but also a teacher’s personality which ensures formation of students’ needs and interests, motives and aims that activate their activity.